2017
DOI: 10.31603/cakrawala.v12i2.1842
|View full text |Cite
|
Sign up to set email alerts
|

Jilbab Sebagai Etika Busana Muslimah dalam Perspektif Al-Qur’an

Abstract: Al Qur'an is the holy book of Islam, in which there are many rules of Allah, one of which is the rule about the ethics of Muslim women wearing Jilbab. God's command of the veil contained in the Qur'an always begins with the words of a believing woman. this phrase shows how the hijab's position is based on the faithful women. According to Abdul A'la Al-Maududi as quoted by Quraish Shihab, the basis of all forms of obedience and obedience in Islam is Faith. It is clear that it is faith alone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
15

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 1 publication
0
2
0
15
Order By: Relevance
“…Regarding the procedures and manners of a Muslim woman in dressing according to Islamic law, it was concluded that Muslimah clothing must cover the genitals and be able to keep the wearer from the negative effects (Fauzi, 2016). In her historical study of headscarves as Muslimah clothing ethics, Wijayanti (2017) argued that the use of headscarves is not a Khilafah matter, because the scholars of the interpretation (tafsir) expert from the past until now have agreed to it as an obligation for Muslim women. The order is based on the arguments, both from the Qur'an and the hadith and qarinah (instructions) that are very strong.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the procedures and manners of a Muslim woman in dressing according to Islamic law, it was concluded that Muslimah clothing must cover the genitals and be able to keep the wearer from the negative effects (Fauzi, 2016). In her historical study of headscarves as Muslimah clothing ethics, Wijayanti (2017) argued that the use of headscarves is not a Khilafah matter, because the scholars of the interpretation (tafsir) expert from the past until now have agreed to it as an obligation for Muslim women. The order is based on the arguments, both from the Qur'an and the hadith and qarinah (instructions) that are very strong.…”
Section: Introductionmentioning
confidence: 99%
“…Hijab is a symbol of honor for Muslim women, both physically and mentally. It is their faith that makes them wear the hijab voluntarily (Wijayanti, 2017). This faith is the main basis for obedience in carrying out Islamic teachings.…”
Section: Resultsmentioning
confidence: 99%
“…Sebaiknya dalam membahas ajaran menutup aurat atau berhijab, yang diutamakan adalah persoalan iman setiap individu, dalam hal ini adalah wanita. Sebab iman adalah dasar dari segala perintah Rasul untuk ditaati, termasuk di dalamnya ajaran cara berpakaian dan menutup aurat (Wijayanti, 2017).…”
Section: Hasil Dan Pembahasanunclassified